Science Literacy Profile Science Literacy Profile in Science Learning Solar System Material for Students in Elementary Schools - Wiwin Fida Yanti; Kurnia Prahani, Binar; Suryanti (Elementary Teacher Education Program, Majalengka University, 2024)
Students need to know how much they have learned about scientific principles when studying science. The ability to solve problems, base decisions on science, and use acquired knowledge in everyday life is known as scientific literacy. The aim of this research is to conduct a scientific analysis of scientific literacy skills related to the solar system among students at the Brambang State Elementary School. Seventeen students became the research sample. The data analysis used is quantitative descriptive. Based on observations, research results showed that the scientific literacy skills of Brambang State Elementary School students were very poor, many students had very low scientific literacy skills in learning about the solar system. The results of the student questionnaire also showed that 77% of students still did not understand basic knowledge and concepts of the solar system. The findings of this research can be used as empirical evidence that there is still room for increasing students' scientific literacy at the Brambang State Elementary School in terms of learning about the solar system. Keywords: Scientific Literacy; Science Learning; Solar system